Motor Imagery and Music: The influence of Music on Mental Rotation of bodily-related pictures - Castellar, Fernando (2019)
The pursuit of excellence in sporting practices sheds light on the use of techniques beyond those that pertain to the physical training. Moreover, mental training is now considered a key aspect in an athlete’s training routine, and as a consequence, mental imagery techniques have become popular among athletes and coaches since the mental practice of body movements reportedly improves the actual physical performance. One plausible explanation for this is the overlap between imagery and motor execution in terms of neural substrates activated in the pre-motor and motor cortical areas. Furthermore, music has been associated with enhancement in spatial-temporal reasoning, reflecting on performance in tasks that assess mental imagery processes, and this phenomenon is justified by the hypothesis of a direct cortical activation of areas responsible for spatial-temporal reasoning. It has also been reported that the motor system is actively involved in music processing, in which different patterns of neural activation in the pre-motor and motor cortical areas are elicited according to the rhythmic complexity of a stimulus, strengthening the hypothesis that musical stimuli may be responsible for improvement in motor imagery processes. To investigate this hypothesis, 30 Sports Science students completed a motor imagery-related cognitive task – a mental rotation of bodily-related pictures task - after exposure to three different stimuli (silence, music with complex rhythm and music with simple rhythm). Results showed no differences either in mental rotation performance, casting doubt on the hypothesis of improvement in imagery processes after music listening.